Stimuli-responsively porating gels by condensation. Issue 5 (20th December 2017) - Texter, John; Kuriakose, Naveen; Shendre, Swaroop; Lewis, Kendall; Venkatraman, Sundar; Gupta, Harshit
Abstract : A polyurethane (PU) resin derived from glycerol and hexamethylene diisocyanate and an imidazolium bromide ionic liquid chain terminator yield a stimuli-responsive resin that reversibly porates as a solvation response. Abstract : A polyurethane (PU) resin derived from glycerol and hexamethylene diisocyanate and an imidazolium bromide ionic liquid chain terminator yield a stimuli-responsive resin that reversibly porates as a solvation response.